ABSENCE OF STABLE CARBON ISOTOPE FRACTIONATION OF SATURATED AND POLYCYCLIC AROMATIC HYDROCARBONS DURING AEROBIC BACTERIAL BIODEGRADATION - Mazeas L.; Budzinski H.; Raymond N. (My University, 2002)
Compound-specific stable carbon isotopic composition measurement is a promising discriminative tool for source identification of hydrocarbons in modern environments. Nevertheless, to be considered as a source tracer, the 13C/12C ratio either has to be unmodified or at least modified in a predictable fashion by the different processes affecting hydrocarbons in the environment (photo-oxidation, evaporation, biodegradation, etc.). Possible isotopic fractionations introduced by microbial biodegradation have been investigated in this study. Stable carbon isotopic compositions of saturated hydrocarbons and phenanthrene compounds were stable during the course of a crude oil biodegradation experiment with a marine bacterial community. The 13C/12C ratio of some standard 2-methylphenanthrene also remained constant during the course of a biodegradation experiment with a pure bacterial strain. These results indicate the absence of isotopic fractionation of hydrocarbons during aerobic bacterial biodegradation. Therefore, molecular stable carbon isotopic composition of n-alkanes and PAHs can be used for source identification of these compounds in environmental studies.